1991
DOI: 10.1042/bj2760245
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucose-6-phosphate dehydrogenase synthesis and mRNA abundance in cultured rat hepatocytes

Abstract: Conditions were identified which, for the first time, demonstrate that primary hepatocytes can express the same range of glucose-6-phosphate dehydrogenase (G6PD) synthesis and mRNA as in live rats. Primary hepatocytes were cultured without prior exposure to serum, hormones or carbohydrates. Five modulators implicated in G6PD induction in vivo were examined: insulin, dexamethasone, tri-iodothyronine (T3), glucose and fructose, T3 did not affect G6PD activity, and did not interact with carbohydrate to affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…As a first hypothesis, insulin might remain necessary to induce expression of, or to activate, other enzymes involved in glucose metabolism. Insulin is known to be involved in the short‐term and long‐term regulation of several other enzymes of the glycolytic pathway [22], and, in the pentose phosphate pathway, is involved in the transcriptional activation of the key enzyme glucose 6‐phosphate dehydrogenase [23, 24]. A puzzling element, however, is the low concentration of insulin (0.2 nM) sufficient to achieve expression of the L‐PK gene when active glucokinase is already present.…”
Section: Resultsmentioning
confidence: 99%
“…As a first hypothesis, insulin might remain necessary to induce expression of, or to activate, other enzymes involved in glucose metabolism. Insulin is known to be involved in the short‐term and long‐term regulation of several other enzymes of the glycolytic pathway [22], and, in the pentose phosphate pathway, is involved in the transcriptional activation of the key enzyme glucose 6‐phosphate dehydrogenase [23, 24]. A puzzling element, however, is the low concentration of insulin (0.2 nM) sufficient to achieve expression of the L‐PK gene when active glucokinase is already present.…”
Section: Resultsmentioning
confidence: 99%
“…Further refinements in this type of analysis have demonstrated that hepatocytes from fasted animals contain as little as one molecule of G6PDH mRNA per cell and the level increases in excess of 30 Fritz et al (12), using molecular probes, showed that insulin increased the levels of mRNA encoding G6PDH, confirming earlier studies using in vitro translation assays (28). Subsequent studies (7,9) agreed with these observations and led to the conclusion that insulin is a primary hormone in upregulating expression of G6PDH, presumably at the level of transcription since studies employing the fasting/refeeding paradigm have shown that transcriptional activation of the gene occurs (5,6). A major challenge to molecular endocrinologists is to define, at a molecular level, how insulin increases transcription of this and other insulinregulated genes.…”
Section: Use Of Recombinant Dna Probes For Analysis Of G6pdh Expressionmentioning
confidence: 93%
“…The glucocorticoids have a well-established role in hepatic lipogenesis (reviewed in ref 26) and the hepatocyte cell culture system has been useful in defining the interaction of these hormones with insulin. The glucocorticoids by themselves appear only to modestly increase the activity of the enzyme in hepatocytes (7,9,12,29). However, they clearly in-crease G6PDH mRNA in the presence (7,9,12) or absence (9, 12) of insulin while apparently not affecting the relative rate of enzyme synthesis (28).…”
Section: Use Of Recombinant Dna Probes For Analysis Of G6pdh Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since maximal velocity would rarely, if ever, be obtained, much of the G6PDH potential in AL animals is likely never realized. This may be the result of altered post-translational modifications of G6PDH which are known to occur (35). Accordingly, an increase or decrease in NADPH requirement over a sufficient period of time would be expected to yield a fluctuation in the amount of total enzyme.…”
Section: Discussionmentioning
confidence: 99%